Stakeholder awareness of reintegration practices for incarcerated youth: A cross-national comparison. Issue 1 (2nd November 2020) - O'Neill, Sue C.; Mathur, Sarup R.; Cumming, Therese M.; Griller-Clark, Heather; Strnadová, Iva
Abstract: This study offers a cross-national comparison of stakeholders' awareness of the implementation of reintegration policies and practices for incarcerated youths by juvenile justice agencies. Similarities and differences in perceptions of 14 stakeholders from the US and 20 from Australia were collected and analyzed using a self-report measure. Stakeholders from both countries showed considerable awareness of the implementation of effective policies and practices in the domains of interagency collaboration, team planning, and supporting life skills, but were less aware of the implementation of policies and practices of education and supports during and after transition. A key finding was that communication across agencies is critical to increasing stakeholders' awareness of the implementation of effective policies and practices to enhance the youths' reentry success.